2005
DOI: 10.1111/j.1365-2249.2005.02967.x
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor-transgenic primary T cells as a tool for discovery of leukaemia-associated antigens

Abstract: SummaryIdentification of a broad array of leukaemia-associated antigens is a crucial step towards immunotherapy of haematological malignancies. However, it is frequently hampered by the decrease of proliferative potential and functional activity of T cell clones used for screening procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Since then, many TCRs that target peptide/MHCs derived from tumor- or virus-associated/specific antigens have been cloned and expressed in normal T cells, to redirect T cell specificity, including TCRs targeting the following: an epitope derived from melanoma-associated antigen 3 (MAGE-A3) [33]; melanoma antigen recognized by T cells 1 (MART-1) [34–36]; human immunodeficiency virus (HIV) Gag and Pol antigens [37, 38]; hepatitis C virus (HCV) non-structure protein 3 (NS3) [39]; Epstein-Barr virus (EBV) [40]; latent membrane protein 2 (LMP2) [41]; mouse double-minute 2 (MDM2) [42]; New York esophageal squamous cell carcinoma-1 (NY-ESO-1) [43]; melanoma-associated antigen 1 (MAGE-A1) [44]; glycoprotein 100 (gp100) [45, 46]; tumor protein p53 (P53) [47]; human papillomavirus (HPV) 16E7 [48]; minor histocompatibility antigens (mHag) [49]; minor histocompatibility antigen HA-1 (HA-1) [50]; ubiquitously transcribed tetratricopeptide repeat gene on the Y chromosome (UTY) [51]; ribosomal protein S4, Y-linked (RPS4Y) [52]; tyrosinase [53]; the MHC class-II-restricted dead-box RNA helicase Y (DBY) [54]; cytotoxic T cell (CTL)-recognized antigen on melanoma (CAMEL) [55]; Wilms’ tumor 1 (WT1) [56, 57]; a renal cell carcinoma (RCC) tumor antigen [58]; mouse mastocytoma P815 [59]; and carcinoembryonic antigen (CEA) [60]. Pre-clinical studies of these TCRs have demonstrated that the TCR-transduced T cells can recognize tumor cells expressing the specific antigen with the same MHC alleles.…”
Section: Pre-clinical Studies Of Tcr-t Therapymentioning
confidence: 99%
“…Since then, many TCRs that target peptide/MHCs derived from tumor- or virus-associated/specific antigens have been cloned and expressed in normal T cells, to redirect T cell specificity, including TCRs targeting the following: an epitope derived from melanoma-associated antigen 3 (MAGE-A3) [33]; melanoma antigen recognized by T cells 1 (MART-1) [34–36]; human immunodeficiency virus (HIV) Gag and Pol antigens [37, 38]; hepatitis C virus (HCV) non-structure protein 3 (NS3) [39]; Epstein-Barr virus (EBV) [40]; latent membrane protein 2 (LMP2) [41]; mouse double-minute 2 (MDM2) [42]; New York esophageal squamous cell carcinoma-1 (NY-ESO-1) [43]; melanoma-associated antigen 1 (MAGE-A1) [44]; glycoprotein 100 (gp100) [45, 46]; tumor protein p53 (P53) [47]; human papillomavirus (HPV) 16E7 [48]; minor histocompatibility antigens (mHag) [49]; minor histocompatibility antigen HA-1 (HA-1) [50]; ubiquitously transcribed tetratricopeptide repeat gene on the Y chromosome (UTY) [51]; ribosomal protein S4, Y-linked (RPS4Y) [52]; tyrosinase [53]; the MHC class-II-restricted dead-box RNA helicase Y (DBY) [54]; cytotoxic T cell (CTL)-recognized antigen on melanoma (CAMEL) [55]; Wilms’ tumor 1 (WT1) [56, 57]; a renal cell carcinoma (RCC) tumor antigen [58]; mouse mastocytoma P815 [59]; and carcinoembryonic antigen (CEA) [60]. Pre-clinical studies of these TCRs have demonstrated that the TCR-transduced T cells can recognize tumor cells expressing the specific antigen with the same MHC alleles.…”
Section: Pre-clinical Studies Of Tcr-t Therapymentioning
confidence: 99%
“…A more feasible approach to generate sufficient number of functional T cells for therapeutic transfer has been the production of TCR-transgenic T cells restricted to a particular tumor epitope [92,93]. This approach uses viral transfer of the genes encoding the TCR α and β chains of identified tumor-specific clones into primary T cells.…”
Section: Production Of Bulk T Cells As a Tool For Discovery Of Taamentioning
confidence: 99%
“…Heemskerk and colleagues were the first to describe the transfer of a mHag-specific TCR (HA-2, Heemskerk et al, 2003). Other specificities that have been transferred are HA-1, UTY, and RPS4Y (Ivanov et al, 2005;Mommaas et al, 2005;Ivanov et al, 2006), and the MHC class II restricted DBY (van der Veken et al., 2005). It remains to be shown whether these TCR modified T cells with single antigen specificities are as effective in clinical settings as the allogeneic T cells used for donor lymphocyte transfusions.…”
Section: Tcr Gene-modified T Cellsmentioning
confidence: 96%